If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8z + -1z = -3 + 2z + -3 + -9 Combine like terms: 8z + -1z = 7z 7z = -3 + 2z + -3 + -9 Reorder the terms: 7z = -3 + -3 + -9 + 2z Combine like terms: -3 + -3 = -6 7z = -6 + -9 + 2z Combine like terms: -6 + -9 = -15 7z = -15 + 2z Solving 7z = -15 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 7z + -2z = -15 + 2z + -2z Combine like terms: 7z + -2z = 5z 5z = -15 + 2z + -2z Combine like terms: 2z + -2z = 0 5z = -15 + 0 5z = -15 Divide each side by '5'. z = -3 Simplifying z = -3
| (5k+35)-8=112 | | A=16(10+7) | | x-x+12=0 | | 4(X+4)=6X+16 | | a+9=21 | | -11=11(h-2) | | 1.6(6-v)=10 | | 2x-10=6x-18 | | (7x-8)+(3x+8)=180 | | -x+4=17 | | 2y-9=-23 | | 7.5+2.2n=-5.6 | | (x+5)=49 | | -9(t+2)=0 | | 2x+52=8x-14 | | 14x-7=5+11x | | 17=5q+2 | | -14=3.1(k-4) | | 10+3x=30+4x | | 1-x+6=16 | | 70-6x=39x+20 | | (x-5)(3x-6)=0 | | 5-(4x-5)=-25x-30 | | 2.8(m-5)=-20 | | d=ab^2c+1 | | 7x^2+28x+3=0 | | 18p+=11-3p | | x-x-20=0 | | 2x+(4x+16)=7 | | 3(w-3)=18 | | 8.2=1.9f-2.6 | | 6x^2=168 |